ENTPD8 overexpression enhances anti-PD-L1 therapy in hepatocellular carcinoma via miR-214-5p inhibition - Si-qi Zhao; Min-jie Chen; Fei Chen; Zhao-feng Gao; Xiao-ping Li; Ling-yu Hu; Hai-ying Cheng; Jin-yan Xuan; Jian-guo Fei; Zheng-wei Song (iScience)
Summary: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related deaths globally, with poor prognosis due to late diagnosis and limited treatment options. In this study, we evaluated the expression of ectonucleoside triphosphate diphosphohydrolase 8 (ENTPD8) in HCC tissues and its clinical significance. Immunohistochemistry, The Cancer Genome Atlas (TCGA) data, and single-cell expression analysis revealed reduced ENTPD8 levels in liver cancer compared to adjacent tissues, with ENTPD8 primarily expressed in tumor cells within the tumor tissue. In vitro assays demonstrated that ENTPD8 inhibits HCC cell proliferation, invasion, and migration. Mechanistically, ENTPD8 regulates programmed death-ligand 1 (PD-L1) expression through miR-214-5p modulation. In vivo, ENTPD8 overexpression combined with anti-PD-L1 treatment enhanced therapeutic efficacy in HCC mouse models. These findings suggest that ENTPD8 may serve as a prognostic marker and therapeutic target for HCC, offering potential strategies for improving treatment outcomes.